Wireless Terrestrial Backhaul for 6G Remote Access: Challenges and Low Power Solutions - Saarnisaari, Harri; Chaoub, Abdelaali; Heikkilä, Marjo; Singhal, Amit; Bhatia, Vimal (Frontiers in Communications and Networks, 2021)
Despite developments in communication systems over the last few decades, a digital divide in the unconnected part of the world. The latter is characterised by large distances to internet access points, underdeveloped infrastructure, sparse populations and low incomes. This concern of digital divide is raised in the 6G's initial vision as an extremely important topic. However, it is important to understand affiliated challenges and potential solutions to achieve this vision. Motivated by the recent backhaul link forecasts that expect a dominance of the microwave technology within the backhauling market, this paper studies the potential of a low power terrestrial microwave backhaul from the sufficient data rate and solar powering perspective. Competing technologies (e.g. fiber) may not be energy efficient and commercially viable for global connectivity. Since rural and remote areas may not have grid power, hence we look at the viability of alternative sustainable sources, in particular solar power, to power the wireless backhaul in 6G. In addition, we also explore services for the operators and users to use the system efficiently. Since the access points are connected to backhaul, we also compare the two prominent solutions based on low power small radius cells and a mega-cell that covers a large area, and show insights on the power autonomy of the systems. At the end, we propose directions for research and deployment for an inclusive connectivity as a part of future 6G networks.